EFEKTIVITAS METODE BERNYANYI DENGAN GERAKAN LOKOMOTOR DALAM MENINGKATKAN KEMAMPUAN BAHASA ANAK - Rizki Wahyunita (STIT Al-Washliyah Binjai, 2025)
This research aims to analyze the effectiveness of the singing method with locomotor movements in improving early childhood language skills at Raudhatul Athfal Amanah, Kwala Begumit Village, Binjai District, Langkat Regency. This study used a quasi-experimental design with a pretest-posttest control group design. The research sample consisted of 40 children divided into experimental and control groups. Data were collected using tests, observations, and interviews, and analyzed using descriptive and inferential statistics. The results showed that the experimental group experienced a significant increase in average scores from 64.3 (pretest) to 82.4 (posttest), compared to the control group which increased from 62.7 to 70.8. The singing method with locomotor movements effectively enhanced vocabulary mastery, sentence construction ability, and speaking confidence in early childhood. This method is recommended as an innovative and enjoyable learning strategy in early childhood education settings.